Probing the early Milky Way with GHOST spectra of an extremely metal-poor star in the Galactic disc - Dovgal, Anya (2024)
Pristine 183.6849 + 04.8619 (P1836849) is an extremely metal-poor ([Fe/H] = −3.3 ± 0.1) star on a prograde orbit confined to the Galactic disc. Such stars are rare and may have their origins in protogalactic fragments that formed the early Milky Way, in low-mass satellites accreted later, or forming in situ in the Galactic plane. Here, we present a chemo-dynamical analysis of the spectral features between 3700−11 000 Å from a high-resolution spectrum taken during Science Verification of the new Gemini High-resolution Optical SpecTrograph. Spectral features for many chemical elements are analysed (Mg, Al, Si, Ca, Sc, Ti, Cr, Mn, Fe, Ni), and valuable upper limits are determined for others (C, Na, Sr, Ba). This main sequence star exhibits several rare chemical signatures, including (i) extremely low metallicity for a star in the Galactic disc, (ii) very low abundances of the light α-elements (Na, Mg, Si) compared to other metal-poor stars, and (iii) unusually large abundances of Cr and Mn, where [Cr, Mn/Fe]NLTE > +0.5. A comparison to theoretical yields from supernova models suggests that two low-mass Population III objects (one 10 M supernova and one 17 M hypernova) can reproduce the abundance pattern well (reduced χ2 < 1). When this star is compared to other extremely metal-poor stars on quasi-circular, prograde planar orbits, differences in both chemistry and kinematics imply there is little evidence for a common origin. The unique chemistry of P1836849 is discussed in terms of the earliest stages in the formation of the Milky Way